Potential of tipping flush gate for sedimentation management in open stormwater sewer - Bong, Charles Hin Joo; Laub, T.L.; Ghanic, A. Ab. (Taylor, 2016)
This paper presents the design of a tipping flush gate and its potential use in servicing open storm sewers in terms of sedimentation management. The tipping flush gate was installed in a section of open concrete storm sewer located in a commercial area in Taman Pekaka, Nibong Tebal, Penang, Malaysia. Monitoring of the gate operation and performance was done from 14th November 2012 to 15th March 2013 covering the beginning and end of the wet season. The sediment profile inside the sewer was measured after each operation of the gate or rainfall event. Results showed that the gate was effective in reducing naturally accumulated sediment in the chosen sewer section. However, proper litter management is needed if the gate is to be implemented in open storm sewer systems. A design guideline for the usage of a tipping flush gate for open storm sewers is also presented in this paper.